3D printing the future: scenarios for supply chains reviewed. Issue 10 (6th November 2017) - Ryan, Michael J.; Eyers, Daniel R.; Potter, Andrew T.; Purvis, Laura; Gosling, Jonathan
Abstract : Purpose: The purpose of this paper is to evaluate the existing scenarios for 3D printing (3DP) in order to identify the "white space" where future opportunities have not been proposed or developed to date. Based around aspects of order penetration points, geographical scope and type of manufacturing, these gaps are identified. Design/methodology/approach: A structured literature review has been carried out on both academic and trade publications. As of the end of May 2016, this identified 128 relevant articles containing 201 future scenarios. Coding these against aspects of existing manufacturing and supply chain theory has led to the development of a framework to identify "white space" in the existing thinking. Findings: The coding shows that existing future scenarios are particularly concentrated on job shop applications and pull-based supply chain processes, although there are fewer constraints on geographical scope. Five distinct areas of "white space" are proposed, reflecting various opportunities for future 3DP supply chain development. Research limitations/implications: Being a structured literature review, there are potentially articles not identified through the search criteria used. The nature of the findings is also dependent upon the coding criteria selected. However, these are theoretically derived and reflect important aspect of strategic supply chain management. Practical implications: Practitioners may wish to explore the development of business models within the "white space" areas. Originality/value: Currently, existing future 3DP scenarios are scattered over a wide, multi-disciplinary literature base. By providing a consolidated view of these scenarios, it is possible to identify gaps in current thinking. These gaps are multi-disciplinary in nature and represent opportunities for both academics and practitioners to exploit.